Mineral phase transformation drives molecular fractionation of dissolved organic matter during organic acid-driven weathering of bauxite residue - Chenglong Lu; Songlin Wu; Fang You; Dingyi Yu; Jitraporn Vongsvivut; Annaleise Klein; Lars Thomsen; David Parry; Ting-Shan Chan; Longbin Huang (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Geochemical factors governing vanadium speciation and mobilisation in technosol eco-engineered from bauxite residue under field conditions - Narottam Saha; Chengyao Ren; David Parry; Longbin Huang (Journal of Hazardous Materials, 2025)

Haloalkalitolerant plants drive alkaline mineral weathering and dealkalization of seawater-treated bauxite residue - Chenglong Lu; Songlin Wu; Long Ma; Fang You; Narottam Saha; Hao Bu; Joseph Fernando; David Parry; Lars Thomsen; Ting-Shan Chan; Longbin Huang (Plant and Soil, 2025)
Background Ecological engineering of tailings into soil-like growth media (i.e., technosol) has emerged as a nature-based solution for soilless rehabilitation of alkaline bauxite residue. However, field applications often result in spatial heterogeneity, where uneven amendment leaves behind highly alkaline and saline BR pockets that limit sustainable rehabilitation. It is hypothesized that haloalkalitolerant plants with roots partially grown in the improved niches render their strong tolerance of BR matrix to form extensive roots-mineral interfaces, generate physical and biochemical modification, and irreversibly neutralize the extremely alkaline pH in BR niches. Methods In this study, seawater-treated BR was used to simulate these residual alkaline matrices. Four plant species, including two halophytes, one haloalkalitolerant native acacia and one glycophytic sorghum grass were cultured in a sand-BR compartment system to simulate field heterogeneity. Results Massive roots-BR interfaces were formed. Root activities at the interfaces accelerated the weathering of alkaline minerals and neutralized alkaline pH to circumneutral. Halophytes (Atriplex nummularia and Chloris gayana) were found to be the most effective in weathering and neutralizing BR, due to their higher capacity to exude low-molecular-weight organic acids rich in carboxyl groups in roots-BR interfaces. The LMWOAs facilitated Na⁺-H⁺ exchange with sodalite and disrupted its structure. Conclusion These interactions stimulated the formation of nanosized amorphous Al-Si-Fe minerals on root surfaces. Plant uptake of liberated Na led to Na depletion in the rhizosphere. Therefore, halophytic species should be included in the field application to eliminate substrate heterogeneity of eco-engineering soil formation for soilless BR rehabilitation. Graphical Abstract The root activities of pioneer plants effectively weather alkaline minerals and neutralize alkaline pH in bauxite residue.

The Relationship Between Perceived Discrimination and Reported Nutrient Intake Among Pregnant Individuals of Minoritized Racial and Ethnic Groups - Tatyana Johnson; Ann K. Kan; Lauren B. Bonner; Linda Van Horn; Kiarri N. Kershaw; William A. Grobman; Karen L. Lindsay; Michelle P. Debbink; Brian M. Mercer; David M. Haas; George R. Saade; Uma Reddy; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Maternal dietary intake among alcohol-exposed pregnancies is linked to early infant physical outcomes in South Africa - Julie M. Hasken; Marlene M. de Vries; Anna-Susan Marais; Wendy O. Kalberg; David Buckley; Charles D.H. Parry; Soraya Seedat; Philip A. May (Reproductive Toxicology, 2023)

John Squire: a leader and seminal contributor to experimental and theoretical muscle research for over 50 years - Pradeep K. Luther; Edward P. Morris; David A.D. Parry; Kenneth A. Taylor (Journal of Muscle Research and Cell Motility, 2023)

50 Years of the steric-blocking mechanism in vertebrate skeletal muscle: a retrospective - David A. D. Parry (Journal of Muscle Research and Cell Motility, 2023)
Fifty years have now passed since Parry and Squire proposed a detailed structural model that explained how tropomyosin, mediated by troponin, played a steric-blocking role in the regulation of vertebrate skeletal muscle. In this Special Issue dedicated to the memory of John Squire it is an opportune time to look back on this research and to appreciate John’s key contributions. A review is also presented of a selection of the developments and insights into muscle regulation that have occurred in the years since this proposal was formulated.

Sodium removal from bauxite desilication product (sodalite) aided by chelating effects of inorganic and organic acids - Sicheng Wang; Tuan Nguyen; Hong Peng; Songlin Wu; David Parry; Anja Urban; Longbin Huang (Journal of Environmental Management, 2023)

A simple and robust approach to Bayesian modelling of overdispersed data - David Fletcher; Peter W. Dillingham; Matthew Parry (Environmental and Ecological Statistics, 2023)

Adaptive growth and acidogenic fermentation performance of haloalkaliphilic bacterial communities enriched from biofilms colonising strongly alkaline and saline bauxite residue - Yuanying Ma; Fang You; David Parry; Anja Urban; Longbin Huang (Science of The Total Environment, 2023)

A predictive model of wheat grain yield based on canopy reflectance indices and theoretical definition of yield potential - João Paulo Pennacchi; Nicolas Virlet; João Paulo Rodrigues Alves Delfino Barbosa; Martin A. J. Parry; David Feuerhelm; Malcolm Hawkesford; Elizabete Carmo-Silva (Theoretical and Experimental Plant Physiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Promiscuous Dimerization Between the Caenorhabditis elegans IF Proteins and a Hypothesis to Explain How Multiple IFs Persist Over Evolutionary Time - Anton Karabinos; Jürgen Schünemann; David A. D. Parry (Journal of Molecular Evolution, 2019)

Can gypsy moth stand the heat? A reciprocal transplant experiment with an invasive forest pest across its southern range margin - Trevor M. Faske; Lily M. Thompson; Nana Banahene; Andi Levorse; Melisa Quiroga Herrera; Kayla Sherman; Sarah E. Timko; Banruo Yang; David R. Gray; Dylan Parry; Patrick C. Tobin; Andrew J. Eckert; et al. (Biological Invasions, 2019)

Water quality guideline values for aluminium, gallium and molybdenum in marine environments - Joost W. van Dam; Melanie A. Trenfield; Claire Streten; Andrew J. Harford; David Parry; Rick A. van Dam (Environmental Science and Pollution Research, 2018)

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

Heterotrophic bacteria in Antarctic lacustrine and glacial environments - Johanna Laybourn-Parry; David Pearce (Polar Biology, 2016)

Localisation of keratin K78 in the basal layer and first suprabasal layers of stratified epithelia completes expression catalogue of type II keratins and provides new insights into sequential keratin expression - Lutz Langbein; Leopold Eckhart; Heinz Fischer; Michael A. Rogers; Silke Praetzel-Wunder; David A. D. Parry; Walter Kittstein; Juergen Schweizer (Cell and Tissue Research, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Characterization of T gene sequence variants and germline duplications in familial and sporadic chordoma - Michael J. Kelley; Jianxin Shi; Bari Ballew; Paula L. Hyland; Wen-Qing Li; Melissa Rotunno; David A. Alcorta; Norbert J. Liebsch; Jason Mitchell; Sara Bass; David Roberson; Joseph Boland; et al. (Human Genetics, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Tissue retention of doxorubicin and its effects on cardiac, smooth, and skeletal muscle function - Reid Hayward; David Hydock; Noah Gibson; Stephanie Greufe; Eric Bredahl; Traci Parry (Journal of Physiology and Biochemistry, 2013)

Trace metal concentrations in the tropical sponge Spheciospongia vagabunda at a sewage outfall: synchrotron X-ray imaging reveals the micron-scale distribution of accumulated metals - Anna Padovan; Niels Munksgaard; Belinda Alvarez; Keith McGuinness; David Parry; Karen Gibb (Hydrobiologia, 2012)

Linkage to chromosome 2q32.2-q33.3 in familial serrated neoplasia (Jass syndrome) - Aedan Roberts; Derek Nancarrow; Mark Clendenning; Daniel D. Buchanan; Mark A. Jenkins; David Duggan; Darin Taverna; Diane McKeone; Rhiannon Walters; Michael D. Walsh; Bruce W. Young; Jeremy R. Jass; et al. (Familial Cancer, 2011)

The role of β-sheets in the structure and assembly of keratins - R. D. Bruce Fraser; David A. D. Parry (Biophysical Reviews, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Seasonal patterns in biomass smoke pollution and the mid 20th‐century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2007)
Aim Globally, most landscape burning occurs in the tropical savanna biome, where fire is a characteristic of the annual dry season. In northern Australia there is uncertainty about how the frequency and timing of dry season fires have changed in the transition from Aboriginal to European fire management. Location In the tropical eucalypt savannas that surround the city of Darwin in the northwest of the Northern Territory of Australia. Methods Our study had three parts: (1) we developed a predictive statistical model of mean mass (µg) of particulates 10 µm or less per cubic metre of air (PM 10 ) using visibility and other meteorological data in Darwin during the dry seasons of 2000 and 2004; (2) we tested the model and its application to the broader air shed by (a) matching the prediction of this model to PM 10 measurements made in Darwin in 2005, (b) matching the predictions to independent measurements at two locations 20 km to the north and south of Darwin and (c) matching peaks in PM 10 to known major fire events in the region (2000–01 dry seasons); and (3) we used the model to explore changes in air quality over the last 50 years, a period that spans the transition from Aboriginal to European land management. Results We demonstrated that visibility data can be used reliably as a proxy for biomass burning across the largely uncleared tropical savannas inland of Darwin. Validations using independent measurements demonstrated that our predictive model was robust, and geographically and temporally representative of the regional airshed. We used the model to hindcast and found that seasonal air quality has changed since 1955, with a trend to increasing PM 10 concentrations in the early dry season. Main conclusions The results suggest that the transition from Aboriginal to European land management has been associated with an increase in fire activity in the early months of the dry season.

Seasonal patterns in biomass smoke pollution and the mid 20th-century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2006)

Small-scale spatial variation in the elemental composition of otoliths of Stegastes nigricans (Pomacentridae) in French Polynesia - Alain Lo-Yat; Mark Meekan; Niels Munksgaard; David Parry; Serge Planes; Marten Wolter; John Carleton (Coral Reefs, 2005)

Colour vision and speciation in Lake Victoria cichlids of the genus Pundamilia - KAREN L. CARLETON; JULIET W. L. PARRY; JAMES K. BOWMAKER; DAVID M. HUNT; OLE SEEHAUSEN (Molecular Ecology, 2005)
Lake Victoria cichlids are one of the most speciose groups of vertebrates. Selection on coloration is likely playing an important role in their rapid speciation. To test the hypothesis that sensory biases could explain species differences in mating preferences and nuptial coloration, we studied seven populations of four closely related species of the genus Pundamilia that differ in visual environment and male nuptial colour. Microspectrophotometry determined that the wavelength of maximum absorption (λ max ) of the rod pigment and three cone pigments were similar in all four species. Only the long wavelength sensitive (LWS) pigment varied among species, with 3–4 nm shifts in λ max that correlated with differences in the LWS opsin sequence. These subtle shifts in λ max coincided with large shifts in male body colour, with red species having longer LWS pigments than blue species. Furthermore, we observed within and between species a correlation between water transparency and the proportion of red/red vs. red/green double cones. Individuals from turbid water had more red/red double cones than individuals from clear water. The variation in LWS λ max and in the proportion of red/red double cones could lead to differences in perceived brightness that may explain the evolution of variation in male coloration. However, other factors, such as chromophore shifts and higher order neural processing, should also be investigated to fully understand the physiological basis of differential responses to male mating hues in cichlid fish.

Association of Fusarium Species in the Wheat Stem Rot Complex - Tim Pettitt; Xiangming Xu; David Parry (European Journal of Plant Pathology, 2003)